0971 Mother's Parenting Style As A Moderator In The Relationship Between Temperament And Sleep Problems In Children With Obesity. (27th May 2020) - Nam, H; Kim, J; Woo, S; Park, S; Lee, H; Jang, H; Park†, K; Suh†, S
Abstract: Introduction: Based on past studies, a child's temperament and parenting style greatly affect a child's sleep. However, there are limited studies that have investigated how parenting styles and a child's temperament interact and affect the child's sleep in obese children. Thus, this study investigated parenting styles as a moderator in the relationship between temperament and sleep in obese children. Methods: Seventy-seven obese children (male=66.2%, average BMI = 27.35±2.78) participated in the study. The mean age of the participants was 10.82(± 1.00) years. The primary caregiver (mother) of the participants completed the Junior Temperament and Character Inventory (J-TCI), and Parents as Social Context Questionnaire (K-PSCQ), and Children's Sleep Habits Questionnaire (CSHQ). Among the different subscales, only Novelty Seeking (NS) and Reward Dependence (RD) were used for analysis among Junior Temperament and Character Inventory (J-TCI) components. Results: In this sample, 66 children (85.7%) reported significant levels of sleep problems based on the CSHQ. Novelty seeking (NS) and reward dependence (RD) significantly predicted sleep problems (B=-.771, p<.05, B=-.683, p<.01). Additionally, mother's negative parenting style moderated the relationship between NS and the child's sleep problem [B=.03, 95% CI=.007, .049] and the relationship between RD and the child's sleep problem [B=.031, 95% CI=.013, .049]. The more negative mother's parenting style, the higher the child's NS or RD scores had a negative effect on sleep. Conclusion: The results of this study show that obese children experience high levels of sleep disturbance. Additionally, the mother's negative parenting style moderated the relationship between temperament and sleep problems in obese children. The results suggest that sleep interventions for obese children should include the mother, especially in children with high novelty seeking and reward dependence. Support: This work was supported by Korea Centers for Disease Control and Prevention & Korea National Research Institute of Health (2019020660E-00)